FORMULATION AND EVALUATION OF MUCOADHESIVE BUCCAL TABLETS OF CARVEDILOL - CHANDARANA, DHAVAL A.; PATEL, KEYUR S.; PATEL, SAMIR C.; PATEL, DEEPA R.; PRAJAPATI, SHAILESH T. (International Journal of Applied Pharmaceutics, 2020)
Objective: The aim of the study was to formulate and evaluate mucoadhesive buccal tablets of carvedilol to avoid the first-pass metabolism. Methods: Mucoadhesive Buccal tablets of carvedilol were prepared by direct compression techniques using a combination of bioadhesive polymers such as hydroxypropyl cellulose (HPC) and polyethlyelne oxide WSR-1105 (PEO WSR-1105). In order to improve solubility of carvedilol, solid dispersion was prepared using poloxamer 188. A 32 Full factorial design was applied to investigate the combined effect of the two independent variables i.e. concentration of HPC (X1) and concentration of PEO WSR-1105(X2) on the dependent variables, % in vitro drug release at 1 h (Y1), % in vitro drug release at 4 h (Y2), mucoadhesive strength (Y3) and mucoadhesion time (Y4). Results: Optimized mucoadhesive buccal tablets shows in vitro drug release of 96.23±2.45 in 8 h, mucoadhesive strength of 18.20±1.44 g, mucoadhesion time 420±2.6 min and surface pH 6.75±0.015. Drug excipients compatibility study by FTIR showed no interaction between drug and excipients. Conclusion: From all parameters and experimental design evaluation, it was concluded that the drug release rate decreased with an increase the concentration of HPC and PEO WSR-1105 and mucoadhesion property increased with increase the concentration of PEO WSR-1105. The in vitro release kinetics revealed the Korsmeyer-Peppas model is followed and drug release is by anomalous diffusion.